1963
DOI: 10.1139/b63-101
|View full text |Cite
|
Sign up to set email alerts
|

Ascospore Discharge and Conidium Release by Nectria Galligena Bres. Under Field and Laboratory Conditions

Abstract: Ascospore discharge and conidium release of Nectria galligena Bres. from cankers on yellow birch (Betula alleghaniensis Britt.) were investigated under field conditions and were related to prevailing rainfall, relative humidity, and temperature. Release of conidia was associated with splashing rain whereas ascospores were discharged during or after rain. Conidia were trapped only from May through August during the period of active growth of the host, and showed a peak in May and June. In contrast, ascospores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
2

Year Published

1971
1971
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 2 publications
1
8
1
2
Order By: Relevance
“…Spore discharge, however, was more closely related to the number of hours of leaf wetness than to the volume of precipitation, and differences in seasonal spore discharge between localities with similar levels of rainfall might be due to this factor. Lortie & Kuntz (1963) found that wetted perithecia discharged their spores only after 2-3 h in a dry atmosphere (Iess than 90 % r.h.), and that no discharge occurred whilst the perithecia remained wet. That relatively few ascospores were collected in this study on days with more than 16 h leaf wetness was presumably due to the lack of an adequate drying period for discharge on those days.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Spore discharge, however, was more closely related to the number of hours of leaf wetness than to the volume of precipitation, and differences in seasonal spore discharge between localities with similar levels of rainfall might be due to this factor. Lortie & Kuntz (1963) found that wetted perithecia discharged their spores only after 2-3 h in a dry atmosphere (Iess than 90 % r.h.), and that no discharge occurred whilst the perithecia remained wet. That relatively few ascospores were collected in this study on days with more than 16 h leaf wetness was presumably due to the lack of an adequate drying period for discharge on those days.…”
Section: Discussionmentioning
confidence: 96%
“…The method used to trap spores was based on techniques described by Munson (1939) and Lortie & Kuntz (1963). Microscope slides (7.5 x 2.5 cm), coated with a mixture of petroleum jelly and paraffin wax (50:50), were held parallel to and not more than 2 cm from the diseased areas of bark by metal brackets fixed to the branch by a screw clip.…”
Section: Materials a N D M E T H O D Smentioning
confidence: 99%
“…Wood and French (1962) reporting ascospore discharge by Hyyoxylorz pruitlatwn during winter in Minnesota found the bark temperature on aspen commonly 10 to 15°C higher than the ambient air temperature, even when air temperature was -5°C. Lortie and Kuntz (1963) also reported ascospore discharge from Nectria cankers on yellow birch at near-freezing temperatures during periods of relatively mild weather from late November through March in Quebec. It thus seems that temperatures above freezing do not impede completely spore discharge but probably only slow down both the processes of spore production and discharge.…”
Section: Discussionmentioning
confidence: 85%
“…Bulit (1957), Lortie et Kuntz (1963) pour N. galligena, Parker (1974 Nous n'avons pas retrouvé l'antagonisme dans la production des deux types de spores montré par Bulit provenant sans doute de l'imprécision avec laquelle nous avons appréhendé l'émission conidienne. L'abondance des macroconidies dans les eaux s'écoulant le long des troncs, le peu de temps nécessaire à leur germination font de ces spores des organes de choix pour la multiplication des chancres sur une même tige.…”
Section: Resultsunclassified
“…(macroconidies et ascospores), agent d'un chancre chez le hêtre, tout au long de l'année. Cette relation est commune à toutes les espèces de Nectria étudiées à ce jour (N. galligena, Bulit, 1957 ;Lortie et Kuntz, 1963 ;N. coccinea, Parker, 1974).…”
Section: Discussionunclassified